2012
DOI: 10.1016/j.thromres.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor/Factor VIIa Complex: Role of the Membrane Surface

Abstract: Blood clotting is triggered when the plasma serine protease factor VIIa binds to the cell-surface protein, tissue factor (TF); the resulting TF:FVIIa complex activates factors IX (FIX) and X (FX) by limited proteolysis. FVIIa, FIX and FX all bind reversibly to membranes via their gamma-carboxyglutamate-rich (GLA) domains, while TF is an integral membrane protein. Removing these proteases from the membrane surface is known to render them thousands of times less active, although the mechanisms by which blood clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The coagulation factor X binding to Nanodiscs assembled with POPC:POPS mixtures of different compositions, from 0 to 90% PS lipid, showed that maximum affinity is reached at 80% PS, and the maximum rate of Factor X activation by the complex of tissue factor and Factor VIIa is observed at 70% PS 91 . This observation confirmed the idea of preferential activation of Factor X on PS-rich clusters, the formation of which may be favored by the presence of divalent cations 263 .…”
Section: Application Of Nanodiscs In Functional Studies Of Membransupporting
confidence: 85%
“…The coagulation factor X binding to Nanodiscs assembled with POPC:POPS mixtures of different compositions, from 0 to 90% PS lipid, showed that maximum affinity is reached at 80% PS, and the maximum rate of Factor X activation by the complex of tissue factor and Factor VIIa is observed at 70% PS 91 . This observation confirmed the idea of preferential activation of Factor X on PS-rich clusters, the formation of which may be favored by the presence of divalent cations 263 .…”
Section: Application Of Nanodiscs In Functional Studies Of Membransupporting
confidence: 85%
“…Beyond providing a simple system for assessing Nanodisc assembly, “empty” Nanodiscs of precise lipid composition have found broad utility in probing protein-lipid interactions of fundamental importance to several biological processes, including the blood coagulation cascade. 4345 Nanodiscs were formed using either 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) or 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), and two different MSPs (MSP1D1 or MSP1E3D1). MSP1D1 results in Nanodiscs 9.7 nm in diameter with 120 to 160 lipids per Nanodisc and a lipid:MSP ratio of 60:1 to 80:1 (there are two MSPs per Nanodisc), depending on the packing density of the lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Findings of these studies have been reviewed recently by Morrissey et al. [58,59] and will not be discussed in detail here unless they are relevant for understanding how PS could regulate TF‐FVIIa activity at the cell surface. Although studies in artificial membranes with defined lipid content are useful for understanding the potential effects of phospholipids on TF activity, they may not accurately reflect the behavior of complex cell membrane surfaces.…”
Section: Potential Mechanisms By Which Ps Regulates Tf‐fviia Coagulanmentioning
confidence: 99%